2018
DOI: 10.1136/bcr-2018-225231
|View full text |Cite
|
Sign up to set email alerts
|

Fatal case of macrophage activation syndrome (MAS) in a patient with dermatomyositis and cytomegalovirus (CMV) viraemia

Abstract: We describe a case of an adult with dermatomyositis (DM) who presents with a rash, high fevers, tachycardia and hypotension, initially concerning for an infectious aetiology or a DM flare. She was found to have cytomegalovirus viraemia which improved after starting valganciclovir. After extensive workup and lack of improvement with broad-spectrum antimicrobial therapy, intravenous immunoglobulin and steroids, the patient was diagnosed with macrophage activation syndrome after bone marrow biopsy and levels of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…In the present study, we have demonstrated for the first time that 10.9% of dermatomyositis patients were complicated with MAS. Consistent with our result, MAS may occur in patients with dermatomyositis but has only been described previously in case reports 16 , 17 , 18 , 19 , 20 and small case series. 21 , 22 Our results highlight the clinical and laboratory features and the high mortality rate of MAS in adult dermatomyositis patients.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we have demonstrated for the first time that 10.9% of dermatomyositis patients were complicated with MAS. Consistent with our result, MAS may occur in patients with dermatomyositis but has only been described previously in case reports 16 , 17 , 18 , 19 , 20 and small case series. 21 , 22 Our results highlight the clinical and laboratory features and the high mortality rate of MAS in adult dermatomyositis patients.…”
Section: Discussionsupporting
confidence: 93%
“…4,5 In adults, MAS is most prevalent in patients with adult onset Still's disease (AOSD) and systemic lupus erythematosus (SLE). 6,7 Due to increasing awareness, MAS was more frequently reported in dermatomyositis (DM), 8 rheumatoid arthritis 9,10 and Sjögren's Syndrome (SS). 11 The exact incidence of MAS in rheumatic diseases is unknown.…”
mentioning
confidence: 99%
“…Dermatomyositis (DM) is an autoimmune disease characterized by typical rash and proximal muscle weakness, and the clinical manifestations of the skin include Gottron's rash, positive rash, V-shaped sign, and mechanic hands.In addition, laboratory ndings include increases in muscle enzymes and in ammatory markers, such as lactate dehydrogenase (LDH), creatine kinase (CK), creatine kinase isoenzyme (CKMB), myoglobin (MYO), erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP).Histopathologically, muscle biopsies of DM were characterized by the presence of in ammatory cell in ltrates in the perivascular, perimysial, and endomysium [1].At the same time, DM can also involve other important organs, such as the lungs, heart, kidneys and gastrointestinal tract.It is worth noting that cardiac involvement is not associated with DM severity and can occur at all stages of the disease, but asymptomatic cardiac involvement can be detected in up to 50% of DM patients, and myocardial involvement can lead to possible sudden death such as arrhythmias and extensive microthrombi, which are easily overlooked in clinical practice [2,3].Recently, some epidemiological studies have shown that DM patients have a higher risk of atherosclerosis and myocardial infarction and are common causes of death compared to the general population [4][5][6].Evidence from clinical practice and evidence-based medicine suggests that dysphagia, dysphonia, and aspiration often indicate pharyngeal and esophageal striated muscle involvement, and patients tend to have a poor prognosis [7].There is increasing evidence that DM patients with anti-MDA5 antibodies are more likely to develop rapidly progressive interstitial lung disease, and this antibody is only detected in DM and amyopathic dermatomyositis (ADM) [8], while MDA5 + DM patients have other complications, including pneumomediastinum, macrophage activation syndrome (MAS), and spontaneous intramuscular hemorrhage.These complications have previously been reported to be rare but fatal, and are of particular clinical concern: 80% of MAS occur within 3 months of DM onset, and the mortality rate of DM with MAS is much higher than that of systemic lupus erythematosus and adult Still 's disease [9,10].MAS is known to be a secondary form of hemophagocytic syndrome (HPS), a life-threatening hyperin ammatory syndrome associated with autoimmune diseases [11,12].Patients with MAS can present with various symptoms, such as spiking fever, splenomegaly, cytopenias, coagulopathy, and methaproteinemia, while increases in sIL-2R and decreases in NK cell activity can also be observed [13].Continuously, MAS has been found to be a process characterized by excessive cytokine release and excessive activation of macrophages and T lymphocytes [14].Several studies have shown that elevated circulating cytokines, including IL-1, IL-6, IL-18, IFNs, and TNF, are associated with the pathogenesis of MAS and cause cytokine storm syndrome.In addition, activated macrophages in MAS are also closely associated with IFN-γ, which induces the production of a series of cytokines and is sequentially regulated by cytokines [15]…”
Section: Introductionmentioning
confidence: 99%